Exploring students' mathematical reasoning in solving HOTs problems based on thinking styles - Marufi Marufi; Muhammad Ilyas; Nur Wahidin Ashari; Tri Bondan Kriswinarso; Salwah Salwah (CV. FOUNDAE, 2024)
Background: The advancement of technology has facilitated rapid access to information, yet it poses challenges in discerning accurate information. In this context, critical thinking becomes essential for analyzing and evaluating information. Within mathematics education, exploring students reasoning processes and their alignment with thinking styles is crucial for enhancing problem-solving skills, especially in addressing Higher Order Thinking Skills (HOTS) problems.Aims: This study aims to describe students' mathematical reasoning in solving HOTS problems on the topic of systems of three-variable linear equations, focusing on two distinct thinking styles: Abstract Random and Concrete Sequential.Methods: This qualitative descriptive study was conducted at Cokroaminoto Palopo University with 36 Mathematics Education students. Two subjects, representing each thinking style, were purposively selected based on a thinking style test. Data collection involved mathematical reasoning tests, interviews, and observations, with the researcher serving as the primary instrument.Results: The findings indicate that both Abstract Random and Concrete Sequential subjects demonstrated reasoning abilities that align with all six indicators of mathematical reasoning. Notably, the Abstract Random subject approached problems through hypothesis formation and fractional equations, while the Concrete Sequential subject systematically assigned values and developed mathematical models. Both subjects re-checked their solutions to ensure accuracy.Conclusion: This study concludes that students with both Abstract Random and Concrete Sequential thinking styles exhibit effective mathematical reasoning when solving HOTS problems. These results highlight the importance of tailoring instructional strategies to accommodate diverse thinking styles to enhance students reasoning abilities in mathematics education.